Bicycle helmets are highly effective at preventing head injury during head impact: Head-form accelerations and injury criteria for helmeted and unhelmeted impacts - Cripton, Peter A.; Dressler, Daniel M.; Stuart, Cameron A.; Dennison, Christopher R.; Richards, Darrin (Accident analysis and prevention, 2014)
•Helmets reduced peak accelerations in all impacts.•Helmets reduced HIC in all impacts.•Overall, helmets reduced risk of injury. Cycling is a popular form of recreation and method of commuting with clear health benefits. However, cycling is not without risk. In Canada, cycling injuries are more common than in any other summer sport; and according to the US National Highway and Traffic Safety Administration, 52,000 cyclists were injured in the US in 2010. Head injuries account for approximately two-thirds of hospital admissions and three-quarters of fatal injuries among injured cyclists. In many jurisdictions and across all age levels, helmets have been adopted to mitigate risk of serious head injuries among cyclists and the majority of epidemiological literature suggests that helmets effectively reduce risk of injury. Critics have raised questions over the actual efficacy of helmets by pointing to weaknesses in existing helmet epidemiology including selection bias and lack of appropriate control for the type of impact sustained by the cyclist and the severity of the head impact. These criticisms demonstrate the difficulty in conducting epidemiology studies that will be regarded as definitive and the need for complementary biomechanical studies where confounding factors can be adequately controlled. In the bicycle helmet context, there is a paucity of biomechanical data comparing helmeted to unhelmeted head impacts and, to our knowledge, there is no data of this type available with contemporary helmets. In this research, our objective was to perform biomechanical testing of paired helmeted and unhelmeted head impacts using a validated anthropomorphic test headform and a range of drop heights between 0.5m and 3.0m, while measuring headform acceleration and Head Injury Criterion (HIC). In the 2m (6.3m/s) drops, the middle of our drop height range, the helmet reduced peak accelerations from 824g (unhelmeted) to 181g (helmeted) and HIC was reduced from 9667 (unhelmeted) to 1250 (helmeted). At realistic impact speeds of 5.4m/s (1.5m drop) and 6.3m/s (2.0m drop), bicycle helmets changed the probability of severe brain injury from extremely likely (99.9% risk at both 5.4 and 6.3m/s) to unlikely (9.3% and 30.6% risk at 1.5m and 2.0m drops respectively). These biomechanical results for acceleration and HIC, and the corresponding results for reduced risk of severe brain injury show that contemporary bicycle helmets are highly effective at reducing head injury metrics and the risk for severe brain injury in head impacts characteristic of bicycle crashes.